Use Media Roca (Wheel Read) in Improving Reading Skills in Grade II Students of MIS Aisyiyah - Faiza, Nurul (Journal of General Education Science, 2024)
This research is motivated by the low reading skills in class II of Mis Aisyiyah Wil.Sumut, because teachers do not use media to facilitate the delivery of knowledge to students. This study aims to improve reading skills in class II students of Mis Aisyiyah Wil.Sumut by using ROCA (Reading Wheel) media. The research This is a classroom action research (CAR). This research was conducted in two cycles. The research subjects were 24 second-grade students of Mis Aisyiyah, North Sumatra, consisting of 13 female students and 11 male students. The data collection technique was data use technique test And non test. Instrument study The data used in this study were tests and observation sheets. The data analysis technique used was descriptive quantitative. The results of the study showed that there was an increase in reading skills by applying ROCA (Reading Wheel) media. The increase in reading skills can be seen from the data obtained in cycles I and II. In cycle I, there were 16 students who completed the test with a completion percentage of 66% and 8 students who did not complete it with a completion percentage of 34%. Then in cycle II, 21 students completed the test with a completion percentage of 87% and students who did not complete the test. 3 students did not complete the task with a completion percentage of 13%.